Cell-specific accumulation of maize phosphoenolpyruvate carboxylase is correlated with demethylation at a specific site greater than 3 kb upstream of the gene. - Langdale, J; Taylor, W; Nelson, T (1991)
Development of the C4 photosynthetic pathway relies upon the cell-specific accumulation of photosynthetic enzymes. Although the molecular basis of this cell-specific gene expression is not known, regulation appears to be exerted at the level of transcript accumulation. We have investigated the relationship between gene expression patterns and DNA methylation for genes of two of the C4 photosynthetic enzymes, ribulose bisphosphate carboxylase (RuBPCase) and phosphoenolpyruvate carboxylase (PEPCase). We found no correlation between methylation state and gene expression for either the large subunit or a small subunit gene of RuBPCase. In contrast, demethylation of a specific site 5' to the PEPCase gene was correlated with the light-induced, cell-specific accumulation of PEPCase mRNA. This differentially methylated site is positioned at great distance (greater than 3 kb) from the start of transcription. This observation is made more interesting by the fact that the immediate 5' region of the gene, and some of the coding region, represents an unmethylated CpG island. Such islands are normally associated with constitutively expressed genes.